Intracerebral Hemorrhage Volume Reduction and Timing of Intervention Versus Functional Benefit and Survival in the MISTIE III and STICH Trials. Issue 5 (20th January 2021) - Polster, Sean P; Carrión-Penagos, Julián; Lyne, Seán B; Gregson, Barbara A; Cao, Ying; Thompson, Richard E; Stadnik, Agnieszka; Girard, Romuald; Money, Patricia Lynn; Lane, Karen; McBee, Nichol; Ziai, Wendy; et al.
Abstract: BACKGROUND: The extent of intracerebral hemorrhage (ICH) removal conferred survival and functional benefits in the minimally invasive surgery with thrombolysis in intracerebral hemorrhage evacuation (MISTIE) III trial. It is unclear whether this similarly impacts outcome with craniotomy (open surgery) or whether timing from ictus to intervention influences outcome with either procedure. OBJECTIVE: To compare volume evacuation and timing of surgery in relation to outcomes in the MISTIE III and STICH (Surgical Trial in Intracerebral Hemorrhage) trials. METHODS: Postoperative scans were performed in STICH II, but not in STICH I; therefore, surgical MISTIE III cases with lobar hemorrhages (n = 84) were compared to STICH II all lobar cases (n = 259) for volumetric analyses. All MISTIE III surgical patients (n = 240) were compared to both STICH I and II (n = 722) surgical patients for timing analyses. These were investigated using cubic spline modeling and multivariate risk adjustment. RESULTS: End-of-treatment ICH volume ≤28.8 mL in MISTIE III and ≤30.0 mL in STICH II had increased probability of modified Rankin Scale (mRS) 0 to 3 at 180 d ( P  = .01 and P  = .003, respectively). The effect in the MISTIE cohort remained significant after multivariate risk adjustments. Earlier surgery within 62 h of ictus had a lower probability of achieving an mRS 0 to 3 at 180 d with STICH I and II ( P  = .0004), but not with MISTIE III. This remained significant with multivariate risk adjustments. There was no impact of timing until intervention on mortality up to 47 h with either procedure. CONCLUSION: Thresholds of ICH removal influenced outcome with both procedures to a similar extent. There was a similar likelihood of achieving a good outcome with both procedures within a broad therapeutic time window. Graphical Abstract: